PERBAIKAN KUALITAS BERKELANJUTAN PENYELENGGARAAN AKADEMIK PROGRAM SARJANA ILMU KOMPUTER FMIPA IPB - Rd. Zainal Frihadian; Agus Purwito; Imas Sukaesih Sitanggang (School of Business, Bogor Agricultural University (SB-IPB), 2016)
The quality of a university is not only measured by its academic program inputs but also by its processes, outputs, and outcomes. Performance measurement can be conducted by looking at its achievements at a certain period of time compared with its targets and baseline. It is a fact that the academic implementation of the Undergraduate Program of Computer Science of Faculty of Mathematics and Natural Science IPB is unsatisfactory viewed from the average GPA and study duration during the academic years of 2009-2013. This study aims to to describe the quality of the implementation of the Undergraduate Program of Computer Science and the efforts made by the stakeholders in maintaining and improving the quality and to formulate alternative strategies to obtain better quality. Fishbone analysis method was used to determine the cause of an unsatisfactory average GPA and longer study duration, and descriptive analysis was used to describe the academic quality of the undergraduate program of Computer Science. The results showed the academic quality of the academic year of 2009-2013 has not reached the targets set in the strategic plan, but if seen from the figures, its accomplishments have nearly reached the targets; therefore, it can be said the quality is reasonably good. Constructive efforts in running the academic administration of the study program have also been implemented by the management.Keywords: academic quality, period of study, quality improvement, FMIPA IPB